EU MDR Regulatory Update and Compliance Strategies - Bitrai Chinmai,; Prasanthi D, (Asian Journal of Pharmaceutical Research and Development, 2025)
The formation of the European Union (EU) medical device regulatory framework was largely driven by significant public health crises, including the thalidomide tragedy of the 1950s and 1960s, which revealed the dangers of insufficient oversight in both pharmaceuticals and medical devices. In response, the EU introduced a series of directives, starting with the Medical Device Directive (MDD) in 1993, aimed at harmonizing regulations across member states and ensuring patient safety. Early challenges in these regulations, such as insufficient clinical data and weak post-market surveillance, led to ongoing revisions, particularly as medical technology evolved. The thalidomide disaster highlighted the need for stringent, independent oversight, pushing the EU toward more rigorous standards for clinical evidence, post-market monitoring, and oversight of Notified Bodies independent organizations that assess device conformity.Subsequent medical device failures, such as the PIP breast implant scandal and issues with metal-on-metal hip implants, further exposed gaps in regulation. These prompted the introduction of the Medical Device Regulation (MDR) in 2017, emphasizing enhanced clinical evidence, stricter post-market surveillance, and greater transparency. Key provisions include device classification based on risk, mandatory Unique Device Identification (UDI) for traceability, and a centralized database (EUDAMED) for improved visibility. This ongoing regulatory evolution ensures the safety and efficacy of medical devices across the EU, responding to technological advances and increasing public demand for stronger protections in healthcare.